1981
DOI: 10.1677/joe.0.0890411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced Extracellular Sodium Concentration on the Function of Adrenal Zona Glomerulosa: Studies in Conscious Rats

Abstract: The present experiments were designed to study the effect extracellular hyponatraemia on aldosterone secretion. Hyperaldosteronism was induced by peritoneal dialysis with 5% glucose solution in dexamethasone-pretreated rats. In the narrow physiological range of 135-142 mmol/l, as well as in the whole range of the study (122-142 mmol/l), the plasma concentration of sodium showed a close negative correlation with the serum concentration of aldosterone (r = -0.71 and -0.83, respectively). Plasma renin activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A selective, competitive AVPR2 inhibitor, tolvaptan, is currently in use to counteract the chronic hyponatremia of congestive cardiac failure, cirrhosis, and SIADH (20,29). As noted above, although such conditions are associated with bone loss, now attributable in part to high AVP levels (21,29), we show that, in wild-type and ovariectomized mice, tolvaptan neither offers osteoprotection nor adversely affects bone mass, in essence attesting to its selectivity for the kidney AVPR2.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A selective, competitive AVPR2 inhibitor, tolvaptan, is currently in use to counteract the chronic hyponatremia of congestive cardiac failure, cirrhosis, and SIADH (20,29). As noted above, although such conditions are associated with bone loss, now attributable in part to high AVP levels (21,29), we show that, in wild-type and ovariectomized mice, tolvaptan neither offers osteoprotection nor adversely affects bone mass, in essence attesting to its selectivity for the kidney AVPR2.…”
Section: Discussionmentioning
confidence: 53%
“…The latter is possible because hyperaldosteronism also has been shown to cause bone loss in rodents (29,30). Osteoporosis also is widely recognized as being associated with heart failure, particularly in elderly patients (31); the proposed pathophysiological mechanisms include secondary hyperparathyroidism, testosterone deficiency, and excessive inflammatory cytokine production (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible that the bone loss seen in the patient with SIADH had arisen from a 30-fold elevation in serum AVP levels, although the accompanying high aldosterone may have contributed (19). Hyperaldosteronism has been linked to bone loss in rodents (29,30). The use of spirinolactone in patients with secondary hyperaldosteronism because of heart failure has also been shown to reduce fracture risk (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to vasopressin, this is true for renin (17) and ANP (18), but the idea that osmotic concentration plays a role in the control of aldosterone secretion has not been appropriately considered. Early clinical observations (2, 7) and in vivo experiments (2,4,5) suggested that besides the well-known stimuli like K ϩ , AII, and ACTH, aldosterone secretion may be influenced also by changes in plasma osmolarity. In these studies, [Na ϩ ] and the osmolarity of the blood was markedly altered, and an unexpected dissociation of aldosterone secretion and the activity of the RAS was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia, induced by hemodialysis in anephric man (2) in intact or nephrectomized dogs (3), or induced by peritoneal dialysis in rats after pharmacological inhibition of the renin-angiotensin system (RAS) and ACTH secretion (4), increased plasma concentration of aldosterone (PAC). In peritoneally dialysed, dexamethasone-treated rats with functioning RAS, the plasma concentration of Na ϩ (122-142 mm) correlated negatively with PAC, and the ratio of PAC-to-PRA rose steeply below 132 mm Na ϩ , suggesting that either hyponatremia increases the sensitivity of glomerulosa cells to AII or factors other than RAS may also contribute to the induction of hyperaldosteronism (5). In water-deprived dogs, dehydration was followed by increased PRA without increased PAC (6), and the authors concluded that the induced hypernatremia or hyperosmosis reduced the sensitivity of the adrenal cortex to AII.…”
mentioning
confidence: 96%